Parent and teacher roles in supporting dyslexic learners - Fathonah, Tita Erlina Nur; Wulandari, Murfi’ah Dewi (Journal of Professional Teacher Education, 2025)
The present study aims to examine the role of parents and class teachers in guiding dyslexic children at SD Al-Firdaus Surakarta. The present study employs a qualitative descriptive approach, utilizing data collection methods such as interviews and direct observation. The results of the study on parents of dyslexic children yielded several strategies that are generally implemented, including medical examinations by doctors or experts in the field, the hiring of private tutors, the provision of self-confidence and rewards, and the consistent provision of learning assistance after Maghrib. The results of interviews with teachers indicated that comprehensive support from parents and teachers is imperative for enhancing the motivation and quality of learning in dyslexic children. This support encompasses various forms of assistance, including learning assistance, motivation, and the utilization of relevant learning aids. Special Guidance Teachers (GPKs) also play a crucial role in inclusive education, starting from student identification and assessment, curriculum adaptation, personal assistance, to the development of special programs to improve students' reading skills. This study underscores the significance of collaboration among parents, teachers, and GPK in fostering a conducive and supportive learning environment for children with dyslexia. The following text is intended to provide a comprehensive overview of the subject matter.